Multiculturality and intersectionality in contextual behavioral therapies - Furini, Larissa Gross; Henzel, Gabriela Alsina; Müller, Sara Adaís Ávila Silva; Passos, Jonatas Argemi Foster (Perspectivas em Análise do Comportamento, 2023)
Research in psychology has shown to be limited in regards to the public they represent in relation to researchers and surveyed, which can lead to problematic consequences in working with individuals and multicultural groups. This paper aimed to review in the literature possible interfaces of clinical work addressed to multicultural populations, especially regarding historically oppressed groups, and to propose a broadening of the therapist’s view of themselves and their clients, especially in the context of Contextual Behavioral Therapies, specifically Functional Analytic Psychotherapy (FAP) for its interpersonal characteristic that takes into account both the behavior of clients and the therapist themselves. Therefore, an analysis of the concept of the standpoint theory of the therapeutic dyad is carried out, considering the ADDRESSING cultural competence model, which has dimensions associated with specific intersectional cultural identities relevant to working with multiculturalism. The paper presents a proposal for a new look at case formulation, so that one can consider the different cultures in which clients and therapists are inserted and, ultimately, improve the mental health care of historically oppressed populations.